Relationship between periodontitis, type 2 diabetes mellitus and COVID-19 disease: a narrative review - Muñoz-Carrillo, José Luis; Palomeque-Molina, Paulo Israel; Villacis-Valencia, Marcelo Stalin; Gutiérrez-Coronado, Oscar; Chávez-Ruvalcaba, Francisca; Vázquez-Alcaraz, Silverio Jafet; Villalobos-Gutiérrez, Paola Trinidad; Palomeque-Molina, Josue (Frontiers in Cellular and Infection Microbiology, 2025)
Inflammation plays a fundamental role in the development and bidirectional association of di-verse diseases, such as periodontitis and type 2 diabetes mellitus (T2DM), which generates important clinical complications, where chronic exposure to high levels of blood glucose affects the repair process of periodontal tissues. Likewise, it has been observed that comorbidity, between these two diseases, influences the development of the COVID-19 disease towards a more severe course. However, there is currently very little scientific evidence on the relationship between periodontitis, T2DM and COVID-19 disease. This narrative review aims to provide an understanding of the current and most relevant aspects of the relationship between periodontitis, T2DM and COVID-19 disease. A narrative review was performed through a systematic search of published studies, without date restrictions, indexed in the electronic databases of PubMed, for the inclusion of articles in English, and LILACS for the inclusion of articles in Spanish. This review included different articles, which addressed the most important aspects to present a current perspective on the relationship and influence between periodontitis, T2DM and COVID-19 disease. Comorbidity between periodontitis and T2DM represents a greater risk of developing a more severe course of COVID-19 disease, because these three diseases share three important axes: a clinicopathological axis; an axis associated with glycemia, and an immunological axis associated with inflammation.